Acculturation, Mental Health, and Quality of Life among Hispanic Childhood Cancer Survivors: A Latent Class Analysis - Tobin, Jessica (Ethn Dis, 2018)
OBJECTIVE: Acculturation appears to be an important aspect of the association between ethnicity and disease, but it has not been explored in depth among childhood cancer survivors (CCS). The purpose of our study was to identify distinct acculturative profiles among Hispanic CCS and to assess differences in quality of life and depressive symptoms. DESIGN: Latent class analysis was used to identify distinct acculturative profiles using 9 indicator items reflecting Hispanic and Anglo cultural orientation. Multinomial logistic regression was performed to explore differences in depressive symptoms and quality of life between acculturation classes. SETTING AND PARTICIPANTS: Participants were diagnosed in Los Angeles County, California, USA between 2000-2007 and were recruited for the study in 2009. MAIN OUTCOME MEASURES: Center for Epidemiologic Studies depression scale and the PedsQL 4.0 quality of life scale. RESULTS: Three distinct acculturation classes emerged. All classes displayed a high probability of endorsing all Anglo orientation items. One class additionally demonstrated a high probability of endorsing all Hispanic orientation items and was labeled bicultural 40%); another demonstrated low probability of endorsing the Hispanic items so was labeled assimilated (32%); and the last demonstrated a high probability of endorsing only the Hispanic items related to language use and was labeled linguistically Hispanic/culturally Anglo (LH) (28%). CONCLUSIONS: The assimilated group had significantly more depressive symptoms and lower quality of life than the other two groups. This may indicate that loss of the Hispanic culture may be associated with poorer psychosocial health among CCS.